The Impact of Facilitation on the Quality of Deliberation and Attitude Change. (October 2019) - Kuhar, Metka; Krmelj, Matej; Petrič, Gregor
Many researchers claim that facilitation is a determining factor, if not a necessary condition, for successful deliberative discussion, but little research has applied randomized experimental designs to empirically test such claim. This article analyzes the effect of professionally facilitated versus non-facilitated discussions in a real-life context on participants' attitudes and the perceived quality of group deliberation, controlling for various individual- and group-level variables. We conducted 26 deliberative discussions with 226 teachers from 13 primary schools on the topic of school discipline measures. We assessed the teachers' post-discussion perceptions of the perceived quality of the group deliberation and their attitudes toward school discipline measures pre- and post-discussion. The results show the facilitation's significant influences on attitude change and the perceived quality of the group deliberation. Quality of deliberation is also influenced by heterogeneity of restorative attitudes in discussion groups, whereas attitude change is to a large extent determined also by pre-discussion attitudes.